HUMOR TRANSLATION ON COMEDY FILM SUBTITLE - Maharani, Sang Ayu Isnu; Ediwan, I Nyoman Tri (International Journal of Linguistics and Discourse Analytics, 2019)
Translation can be defined as a product and process. The product refers to the result of translation from the source language to the target language, while the process refers to the activity of translating the source language into the target language. Translation is needed in a growing community in the global era. In this era, the role of media plays significant part in every aspect of human life. Electronic media as one medium for delivering information has the responsibility to convey the latest information not only from within the country but also abroad and throughout the world. The information referred to is not only related to sharing news but also entertainment; one of them is film. Films from abroad (America and Britain) are imported into Indonesia for economic and social purposes.